The COVID-19 Pandemic through the Eyes of Italian Young Hikikomori - Marianna Coppola; Giuseppe Masullo (Culture e Studi del Sociale)
The health and socio-economic crisis induced by COVID-19 has upset the political struc-tures of the worlds governments, which had to respond to an unprecedented health emer-gency. This shifted attention to the issue of internal control: the danger comes not only from outside but is related to the citizens compliance with social distancing norms and, more generally, with the various measures to prevent the spread of. COVID-19 is today pivotal for rethinking oneself, ones future, having acquired an immanent quality for the dis-courses on the meaning of reality. It is even truer for those whose self and actions have been highlighted with the pandemic moment, as the hikikomori, whose voluntary self-isolation and living mostly within media spaces is now a generalized condition. The first section of this contribution will discuss the Italian hikikomori phenomenon through a criti-cal reading of Mazzettis essay: Hikikomori - Il viaggio bloccato dell'eroe. Un punto di vista sociologico (The Heros Blocked Journey. A Sociological Point of View). The second sec-tion will summarise the results of a netnographic survey on the psychological, social, and imaginary dimensions of young Italian hikikomori on COVID-19 containment measures during the first lockdown, between March and May 2020.